Measurement of the dispersion relation for random surface gravity waves. (4th February 2015) - Taklo, Tore Magnus A.; Trulsen, Karsten; Gramstad, Odin; Krogstad, Harald E.; Jensen, Atle
Abstract: We report laboratory experiments and numerical simulations of the Zakharov equation, designed to have sufficient resolution in space and time to measure the dispersion relation for random surface gravity waves. The experiments and simulations are carried out for a JONSWAP spectrum and Gaussian spectra of various bandwidths on deep water. It is found that the measured dispersion relation deviates from the linear dispersion relation above the spectral peak when the bandwidth is sufficiently narrow.